Selection of Hydrographic Objects in NHD 100K Streams from NHD 24K Streams using Drainage Networks Derived from Digital Elevation Models - Mirzayev, K.; Gokgoz, T. (SCITEPRESS, 2022)
The hydrographic objects in 100K NHD (National Hydrographic Dataset) are conventionally derived by generalization. Besides, drainage networks may also be derived from the digital elevation models according to the stream thresholds. This study aims to derive the streams in 100K NHDs from 24K NHDs by means of drainage networks derived from a 10 m resolution digital elevation models. For this purpose; 1) 24K streams corresponding to 100K streams, 2) 24K streams as many as the number of 24K streams corresponding to 100K streams, 3) 24K streams as many as the number of objects calculated by Topfer's formula, and 4) 24K streams as many as the number of midpoints of 24K streams corresponding to 100K streams are selected by means of drainage networks derived from a 10 m resolution digital elevation model. Twelve experiments were conducted to test the suitability of the four approaches in three sub basins (i.e. Big Run, Seneca and Strait in South Branch Potomac Basin in the WV. USA) chosen as the study areas. As a result, none of the approaches was able to select all 24K streams corresponding to 100K streams without any over- or under-represented 24K streams.
Keywords: Cartographic Generalization; Hydrographic Objects; Digital Elevation Models; Hydrologic Analysis; Drainage Networks; Computer Science; Physical Geography; Remote Sensing